2017
DOI: 10.1016/j.envres.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The methylation levels of the H19 differentially methylated region in human umbilical cords reflect newborn parameters and changes by maternal environmental factors during early pregnancy

Abstract: H19 is a tumor-suppressor gene, and changes in the methylation of the H19-differential methylation region (H19-DMR) are related to human health. However, little is known about the factors that regulate the methylation levels of H19-DMR. Several recent studies have shown that maternal environmental factors during pregnancy, such as smoking, drinking, chemical exposure, and nutrient intake, can alter the methylation levels of several genes in fetal tissues. In this study, we examined the effects of maternal fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 53 publications
0
38
0
Order By: Relevance
“…The direction of this association was unexpected since the overexpression of H19 LncRNA in lung tumor is often correlated with hypomethylation of the promoter region CpGs (Kondo et al 1995). H19 LncRNA belongs to a highly conserved imprinted gene cluster that plays important roles in embryonal development and growth control (Gabory et al 2010) and H19 region methylation has been found to be influenced by early life exposures, including maternal factors during pregnancy (Miyaso et al 2017), suggesting the possibility that external exposures could impact H19 methylation. Since the blood samples were drawn years before cancer diagnosis in this study, the methylation patterns we observed could be regions that are modulated early on in lung cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…The direction of this association was unexpected since the overexpression of H19 LncRNA in lung tumor is often correlated with hypomethylation of the promoter region CpGs (Kondo et al 1995). H19 LncRNA belongs to a highly conserved imprinted gene cluster that plays important roles in embryonal development and growth control (Gabory et al 2010) and H19 region methylation has been found to be influenced by early life exposures, including maternal factors during pregnancy (Miyaso et al 2017), suggesting the possibility that external exposures could impact H19 methylation. Since the blood samples were drawn years before cancer diagnosis in this study, the methylation patterns we observed could be regions that are modulated early on in lung cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 16 studies included, 5 studies were RCTs [ 17 , 18 , 19 , 20 , 21 , 26 ] and 11 studies were cohort studies [ 3 , 4 , 6 , 12 , 13 , 14 , 16 , 22 , 23 , 24 , 25 ]. In total, 3617 mother–offspring pairs were included.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 3617 mother–offspring pairs were included. Seven studies included participants from the USA [ 3 , 4 , 6 ], two from the United Kingdom (UK) [ 14 , 17 ], two from Ireland [ 18 , 19 ] and the rest of the studies included participants from China [ 24 ], Japan [ 16 ], Argentina [ 20 ], Denmark [ 21 ] and Scotland [ 13 ]. Two studies included data from the same RCT that investigated epigenetic changes at birth and at 5 years of age in offspring of mothers on a low glycemic index diet (Geraghty et al [ 19 ] and Geraghty et al [ 18 ], respectively).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, demethylation of H19 was associated with growth-related syndromes in human: hypomethylation of H19 being described in Silver-Russell Syndrome, characterized by severe intrauterine and postnatal growth retardation among other clinical features [ 33 ]. The study of samples from umbilical cord, reflecting maternal exposure to environmental adverse factors, indicated that reduced H19 -DMR methylation was related to decreased head circumference in newborns [ 34 ]. Whereas in a case-control study, examination of stillborn brain tissue from diagnosed NTDs revealed the hypermethylation of H19 compared with controls [ 35 ], which is not consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%